2010
DOI: 10.1063/1.3334730
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport and low-temperature scanning tunneling microscopy of microsoldered graphene

Abstract: Using the recently developed technique of microsoldering, we perform systematic transport studies of the influence of PMMA on graphene revealing a doping effect of up to ∆n = 3.8×10 12 cm −2 , but negligible influence on mobility and hysteresis. Moreover, we show that microsoldered graphene is free of contamination and exhibits very similar intrinsic rippling as found for lithographically contacted flakes. Finally, we demonstrate a current induced closing of the previously found phonon gap appearing in scannin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…However, when graphene is deposited on an insulating substrate such as SiO 2 its properties are modified due to defects, strain, inhomogeneous doping and trapped charges [16][17][18] . These altering effects are responsible for a wide range of non-intrinsic spectra reported in the literature for graphene samples deposited on SiO 2 substrates 16,17,19 .…”
mentioning
confidence: 99%
“…However, when graphene is deposited on an insulating substrate such as SiO 2 its properties are modified due to defects, strain, inhomogeneous doping and trapped charges [16][17][18] . These altering effects are responsible for a wide range of non-intrinsic spectra reported in the literature for graphene samples deposited on SiO 2 substrates 16,17,19 .…”
mentioning
confidence: 99%
“…In figure 3, the measured graphene channel resistance (R) as a function of back gate voltage bias (V BG ) is shown with Si substrate used as the back gate for the GFET. The Dirac point (V Dirac ) of the CVD-assembled graphene on h-BN exhibits weak n-type doping possibly due to the PMMA residue introduced during the graphene transfer process [10]. Figure 4 shows the graphene inverter composed of a pair of two GFETs and schematic view.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…11.2 (b). Previous study using scanning tunneling microscopy has shown that this thin layer of PMMA residue typically has a thickness of 1 to 2 nm (Geringer et al ., 2010 ). Generally, an increase of transfer or lithography times causes more PMMA to accumulate on the graphene.…”
Section: Transfer-induced Metal and Molecule Adsorptionsmentioning
confidence: 98%